Alice Ruth Moore Dunbar-Nelson’s Activist Literature - Zagarell, Sandra A (Research in African literatures, 2025)
This article illuminates how the meshing of key aspects of Alice Ruth Moore Dunbar-Nelson’s life and work—writing political activism, teaching—has been obscured by American literary studies’ traditional overreliance on three related assumptions: that diachronicity suffices in accounts of an author’s life, that periodization suffices in accounts of literary history, and that authors are coherent beings. Discussing a range of Dunbar-Nelson’s work—an early sketch, an essay, and published and unpublished fiction— this essay combines synchronicity and diachronicity to engage with the multi-facetedness of her writing about such issues as racial identity and Black involvement in U.S. political parties.